Pengaruh Pembelajaran Mendalam Berbasis Problem Based Learning terhadap Kemampuan Pemecahan Masalah Matematis Siswa Kelas X - Aini, Ida Nur; Sulistyaningrum, Heny (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2026)
This study analyzes the impact of implementing the Problem Based Learning (PBL) model, which emphasizes deep learning, on students' mathematical problem-solving skills, given the ongoing difficulties faced by tenth-grade students at SMAN 3 Tuban in the 2025/2026 academic year regarding selecting critical information, synthesizing concepts, and applying knowledge to real-world situations. Utilizing a quantitative approach with a quasi-experimental, nonequivalent control group design, this research assesses the effectiveness of the model by assigning class X-D as the experimental group and X-E as the control group, each comprising 36 students selected via cluster random sampling. Data processing was conducted using normality tests, homogeneity tests, and Independent Sample t-tests based on the results of pretest and posttest essay assessments. The findings indicate that H₀ is rejected and H₁ is accepted, with the mean posttest score of the experimental group significantly outperforming that of the control group at a significance level of 0.000 (< 0.05), thereby confirming that the deep learning-oriented PBL model has a significant impact on enhancing students' mathematical problem-solving proficiency.